Peningkatan Keterampilan Menulis Artikel Ilmiah Melalui Metode NLP : (Neuro Linguistik Programming) - Adelina M Aritonang; Herlide Purba; Pebryna Riosa Siburian; Mantasia Hasibuan; Ika Febriana (PUSTAKA: Jurnal Bahasa dan Pendidikan, 2024)
Improving Scientific Article Writing Skills Through the NLP (Neuro Linguistic Programming) Method focuses on the use of Neuro Linguistic Programming (NLP) as a strategy to improve the ability to write scientific articles. This research shows that NLP can help improve the quality of scientific writing by improving analysis and synthesis skills, as well as increasing the ability to use language more effectively. The research method used to obtain data To find out whether the research objectives have been achieved, the library method is used, namely using references such as books, journals and others as the main source of research. The results of this research can be used as a reference for scientific writers and teachers in improving their skills in writing scientific articles.